Vitamin D insufficiency and its association with obesity among primary school children in Kuala Lumpur, Malaysia - Khor, Geok Lin; Chee, Winnie S S; Mohd Shariff, Zalilah; Poh, Bee K; Arumugam, Mohan; Ab Rahman, Jamalludin; Theobald, Hannah E (Springer, 2010)
Aims: To present findings on low blood vitamin D status and its association with obesity among primary school children in Kuala Lumpur. Methods: A cross-sectional study of primary aged school children was undertaken in 2008. Six primary schools were randomly selected from a zone in Kuala Lumpur with a multi-ethnic population from middle income levels. Fasting blood samples were taken to assess micronutrients including vitamin D [as 25(OH)D]. A total of 402 boys and girls aged 7–12 years participated in the study. Informed consent was obtained from both parents and the subjects.